Knowledge-intensive economies and opportunities for social, organizational, and technological growth - Lytras, Miltiadis D. 1973-; Daniela, Linda 1967-; Visvizi, Anna 1976- (IGI Global, 2019)
"This book discusses ideas, problems, challenges, and solutions for changes in society brought about by technological innovations. Urban society requires smart, innovative, collaborative learning infrastructures that cultivate a learning culture in the context of 21st century education; where learning goes beyond the space and time context and becomes available everywhere by using different smart educational technologies"--